2018
DOI: 10.1111/1744-9987.12709
|View full text |Cite
|
Sign up to set email alerts
|

Longer‐Period Effects of Bicarbonate/Lactate‐Buffered Neutral Peritoneal Dialysis Fluid in Patients Undergoing Peritoneal Dialysis

Abstract: High concentrations of lactate are considered to contribute to impairment of the peritoneal membrane. We investigated the longer-period effects of bicarbonate/lactate-buffered neutral peritoneal dialysis fluid (PDF) in patients undergoing PD for about 2 years. Patients undergoing PD were changed from a lactate-buffered neutral PDF to a bicarbonate/lactate-buffered neutral PDF. We then investigated the patients' clinical outcomes and peritoneal membrane functions as well as the surrogate markers in the drained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…Our study suggests that Reguneal™ is a biocompatible PDF. Our findings are supported by another recent study, which observed a reduction in markers of peritoneal membrane failure in effluent dialysate after transition from another PDF to Reguneal™ [12]. On the basis of these results, the enhanced biocompatibility of Reguneal™ might ameliorate PDF-induced peritoneal membrane remodeling, and lessen the frequency and severity of peritoneal membrane failure.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Our study suggests that Reguneal™ is a biocompatible PDF. Our findings are supported by another recent study, which observed a reduction in markers of peritoneal membrane failure in effluent dialysate after transition from another PDF to Reguneal™ [12]. On the basis of these results, the enhanced biocompatibility of Reguneal™ might ameliorate PDF-induced peritoneal membrane remodeling, and lessen the frequency and severity of peritoneal membrane failure.…”
Section: Resultssupporting
confidence: 89%
“…In this paper, we examine the biocompatibility of a new PDF in Japan [11,12], and compare this fluid to others that are commercially available in that country. The aim of this study was to compare the basal cytotoxicity of these PDFs, and to assess the relationship between measured basal cytotoxicity and the concentration of both dextrose and glucose degradation products (GDPs) within the different PDFs available in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…One report used the same two PDFs we used and found that bicarbonate/lactate PDF was less toxic to cell viability and apoptosis of PMCs than lactate PDF [12]. In addition, a clinical study [13] reported that Fibrin degradation products and vascular endothelial growth factor concentrations in effluent were lower when using bicarbonate/lactate PDF than when using lactate PDF. From our results and those reports, we consider that bicarbonate/lactate PDF may result in less peritoneal damage than lactate PDF.…”
Section: Discussionmentioning
confidence: 97%
“…157 Other therapeutic approaches mainly focus on new biocompatible PD fluid associated with less peritoneal injury and irritation, thus reducing VEGF production and inhibiting peritoneal neoangiogenesis. 37,38,40 42,158,159…”
Section: Potential Clinical Application Of Antiangiogenic Drugs Targe...mentioning
confidence: 99%